A Ti3C2T x / ZnPc composite gas-sensitive material and its preparation method and application in ammonia detection
By doping nanostructured ZnPc in the Ti3C2Tx gas sensor to form a Ti3C2Tx/ZnPc composite gas-sensitive material, the problem of low ammonia detection sensitivity in the prior art is solved, and high sensitivity detection and good selectivity are achieved.
Patent Information
- Application Number
- CN202211511245.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-11-29
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2042-11-29
AI Technical Summary
In the prior art, Ti3C2Tx gas sensor has low sensitivity to ammonia and cannot effectively monitor ammonia.
Using Ti3C2Tx/ZnPc composite gas-sensitive material, the selectivity and responsiveness of the gas sensor are improved by doping nanostructured ZnPc between the multi-layer Ti3C2Tx.
The response value of the gas sensor to 100ppm ammonia is improved to about 25%, which is significantly better than the individual Ti3C2Tx gas sensor, and has good selectivity and repeatability.
Smart Images

Figure CN116124858B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of gas-sensitive materials, and specifically to a Ti 3 C 2 T x / ZnPc composite gas-sensitive material, preparation method thereof and application in ammonia detection. Background Art
[0002] Ammonia is widely used in various fields, including nitrogen fertilizers, industrial refrigerants, biofuels, and textiles. However, it is one of the most harmful environmental pollutants generated during ordinary industrial production and manufacturing processes. The explosion limit of ammonia is generally 16-25%. According to the standards issued by the Occupational Safety and Health Administration (OSHA) of the United States, the acceptable ammonia concentration for humans is limited to 25ppm when exposed for 8h and 35ppm when exposed for 15 minutes. If humans are exposed to large amounts of ammonia, the skin, eyes, or respiratory system may be affected, leading to blindness and lung diseases. Ammonia is also a natural metabolite of the human body. Excessive ammonia in the exhaled gas of the human body may be caused by several liver and lung-related diseases. Therefore, finding a high-performance ammonia detection sensor is of great significance to production safety and human health.
[0003] In the prior art, there is a method of 3 C 2 T x As a gas-sensitive material for gas sensors, this Ti 3 C 2 T x The gas sensor has low sensitivity to ammonia and cannot effectively monitor ammonia. Summary of the invention
[0004] The present invention aims to provide a Ti 3 C 2 T x / ZnPc composite gas-sensitive material and its preparation method and application in ammonia detection are used to solve the technical problem of low sensitivity of gas sensors in detecting ammonia in the prior art.
[0005] In order to solve the above technical problems, the specific solution adopted by the present invention is: a Ti 3 C 2 T x / ZnPc composite gas-sensitive material, the composite gas-sensitive material is composed of multilayer Ti 3 C 2 T x As the substrate, in the multilayer Ti 3 C 2 T x Interlayer doped nanostructured ZnPc.
[0006] A Ti 3 C 2 T x The preparation method of the ZnPc composite gas-sensitive material comprises the following steps:
[0007] S1. Nanostructured ZnPc and multilayer Ti 3 C 2 T x The mixture was added to ethanol and ultrasonicated to obtain an intermediate solution;
[0008] S2, magnetically stirring the intermediate solution after ultrasonic treatment in S1 at 35-45° C., and filtering to obtain a composite material;
[0009] S3, vacuum drying the composite material at 75-85°C for 10-14h to obtain the Ti 3 C 2 T x / ZnPc composite gas sensing material.
[0010] As a further optimization of the above technical solution, nanostructured ZnPc and multilayer Ti 3 C 2 T x The mass ratio is 1:6 ~ 1:12.
[0011] As a further optimization of the above technical solution, the time of ultrasonic treatment in step S1 is 25 to 35 minutes.
[0012] As a further optimization of the above technical solution, the rotation speed of the magnetic stirring in step S2 is 450-550 rpm, and the stirring time is 0.8-1.2 h.
[0013] As a further optimization of the above technical solution, the multilayer Ti 3 C 2 T x The preparation process is as follows:
[0014] S11, Ti 3 AlC 2 Add to HF and stir magnetically at room temperature for 22-26h;
[0015] S12, centrifuge and wash the mixed solution after magnetic stirring in S11 with deionized water until the pH of the supernatant is between 5.5 and 6.5, remove the supernatant, and collect the lower sediment
[0016] S13, the lower precipitate collected in S12 is vacuum dried at 75-85°C, and the final product is multilayer Ti 3 C 2 T x .
[0017] As a further optimization of the above technical solution, the preparation process of the nanostructured ZnPc is as follows:
[0018] S21, dissolving ZnPc in DMF, and then ultrasonicating;
[0019] S22, adding the solution after ultrasonic treatment in S21 dropwise into deionized water, and stirring to form a ZnPc nanostructure suspension;
[0020] S23, washing the ZnPc nanostructure suspension in S22 with deionized water, ethanol and acetone solution by centrifugation and filtering, and vacuum drying the filtered product at 75-85° C. to obtain nanostructured ZnPc.
[0021] As a further optimization of the above technical solution, in step S22, the solution is added dropwise into deionized water at a rate of 2 ml / min, and stirred at a rotation speed of 600 rpm for 2.8 to 3.2 h.
[0022] A Ti 3 C 2 T x Application of ZnPc composite gas-sensitive materials in ammonia detection.
[0023] As a further optimization of the above technical solution, the Ti as claimed in claim 1 is applied to the sensor ceramic tube of the gas sensor. 3 C 2 T x / ZnPc composite gas sensing material.
[0024] Compared with the prior art, the present invention has the following beneficial effects: 3 C 2 T x The composite of substrate and nanostructured ZnPc improves the performance of Ti 3 C 2 T x The selectivity and uniqueness of nanostructured ZnPc for ammonia. 3 C 2 T x ZnPc nanoparticles are uniformly distributed on the Ti / ZnPc composite gas-sensitive material. 3 C 2 T x The prepared gas sensor has a response value of about 25% to 100ppm ammonia at room temperature, which is the highest under the same conditions. 3 C 2 T x The gas sensor is about 5 times, and Ti 3 C 2 Tx / ZnPc composite gas-sensitive materials also have good selectivity and repeatability, and have potential application value in the fields of toxic gas monitoring and agricultural Internet of Things.
[0025] In Ti 3 C 2 T x The introduction of interlayer spacers similar to nanoparticles (i.e., nanostructured ZnPc) between layers can effectively prevent the restacking effect and increase the Ti 3 C 2 T x Electrochemically active sites on the surface. Metallophthalocyanine has an 18-π aromatic electron cloud that can easily bind to Ti through π-π interactions. 3 C 2 T x Coordination and improved electrochemical response to charge storage by adding one-dimensional nanostructured metal phthalocyanines to Ti 3 C 2 T x In the sheet, it was found that it has a significant enhancement effect on the ion mobility during the electrochemical redox process. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 Where (a, b, c) is Ti 3 C 2 T x / ZnPc SEM image; (d) Ti 3 C 2 T x SEM images of
[0027] Figure 2 Ti 3 C 2 T x / Preparation flow chart of ZnPc gas sensor;
[0028] Figure 3 This is the schematic diagram of the gas-sensitive test system;
[0029] Figure 4 (a) is the XRD pattern of ZnPc; (b) is the XRD pattern of Ti 3 C 2 T x and Ti 3 C 2 T x / XRD pattern of ZnPc;
[0030] Figure 5 Ti 3 C 2 T x 、ZnPc、Ti 3 C2 T x / XPS spectrum of ZnPc;
[0031] Figure 6 (a) is Ti 3 C 2 T x / C1s XPS spectrum of ZnPc; (b) is the C1s XPS spectrum of ZnPc;
[0032] Figure 7 The response curves of four gas sensors to different concentrations of ammonia;
[0033] Figure 8 Ti 3 C 2 T x / Response bar graph of ZnPc gas sensor to 100ppm ammonia at different humidity;
[0034] Fig. 9 Ti 3 C 2 T x / Response bar graph of ZnPc gas sensor to different gases at 100ppm;
[0035] Fig.10 Ti 3 C 2 T x / Response recovery curve of ZnPc gas sensor to 100ppm ammonia;
[0036] Fig.11 Ti 3 C 2 T x Schematic diagram of the repeatability of the ZnPc gas sensor. DETAILED DESCRIPTION
[0037] Example 1
[0038] A Ti 3 C 2 T x The / ZnPc composite gas-sensitive material is prepared according to the following steps;
[0039] 1) Multilayer Ti 3 C 2 T x Preparation
[0040] Take 1g of Ti 3 AlC 2Slowly (about 20 minutes) add it to 20 ml HF and stir it magnetically (500 r / min) at room temperature for 24 hours. Then, the stirred mixture is centrifuged and washed several times with deionized water at a speed of 3500 r / min until the pH of the supernatant is 6. The supernatant is removed, the lower precipitate is collected, and the precipitate is vacuum dried at 80 ° C for 12 hours. The final product is multilayer Ti 3 C 2 T x .
[0041] 2) Preparation of Nanostructured ZnPc
[0042] 2.5 mg ZnPc was dissolved in 2.5 mL DMF, and then the solution was ultrasonically treated (30 min). After that, the solution was added dropwise to 200 mL deionized water at a rate of 2 mL / min (which can be appropriately adjusted) and stirred continuously to form ZnPc nanostructures (3 h, 600 rpm). Finally, the deionized water, ethanol and acetone solutions were centrifuged and washed respectively, and the filtered product was vacuum dried at 80 ° C for 12 h.
[0043] 3) Ti 3 C 2 T x Preparation of ZnPc / ZnPc composite gas-sensitive materials
[0044] Take 2 mg of nanostructured ZnPc and 12 mg of multilayer Ti 3 C 2 T x The mixture was added to 30 mL of ethanol, ultrasonicated for 30 min, and then stirred with a magnet at 40 ° C and 500 rpm for 1 h, filtered to obtain a composite material, and the composite material was vacuum dried at 80 ° C for 12 h to obtain Ti 3 C 2 T x / ZnPc composite gas sensing material.
[0045] Example 2
[0046] A Ti 3 C 2 T x The / ZnPc composite gas-sensitive material is prepared according to the following steps;
[0047] 1) Multilayer Ti 3 C 2 T x Preparation
[0048] Take 1g of Ti 3 AlC 2Slowly (about 20 minutes) add it to 20 ml HF and stir it magnetically (500 r / min) at room temperature for 24 hours. Then, the stirred mixture is centrifuged and washed several times with deionized water at a speed of 3500 r / min until the pH of the supernatant is about 6. The supernatant is removed, the lower precipitate is collected, and the precipitate is vacuum dried at 80°C for 12 hours. The final product is Ti 3 C 2 T x .
[0049] 2) Preparation of Nanostructured ZnPc
[0050] 2.5 mg ZnPc was dissolved in 2.5 mL DMF, and then the solution was ultrasonically treated (30 min). After that, the solution was added dropwise to 200 mL deionized water at a rate of 2 mL / min (appropriately adjustable) and stirred continuously to form ZnPc nanostructures (3 h, 600 rpm can be appropriately adjusted). Finally, it was centrifugally washed with deionized water, ethanol and acetone solutions, and the filtered product was vacuum dried at 80 ° C for 12 h.
[0051] 3) Ti 3 C 2 T x Preparation of ZnPc / ZnPc composite gas-sensitive materials
[0052] Take 2 mg of nanostructured ZnPc and 20 mg of multilayer Ti 3 C 2 T x The mixture was added to 30 mL of ethanol, ultrasonicated for 30 min, and then stirred with a magnet at 40 ° C and 500 rpm for 1 h, filtered to obtain a composite material, and the composite material was vacuum dried at 80 ° C for 12 h to obtain Ti 3 C 2 T x / ZnPc composite gas sensing material.
[0053] Example 3
[0054] A Ti 3 C 2 T x The / ZnPc composite gas-sensitive material is prepared according to the following steps;
[0055] 1) Multilayer Ti 3 C 2 T x Preparation
[0056] Take 1g of Ti 3 AlC 2Slowly (about 20 minutes) add it to 20 ml HF and stir it magnetically (500 r / min) at room temperature for 24 hours. Then, the stirred mixture is centrifuged and washed several times with deionized water at a speed of 3500 r / min until the pH of the supernatant is about 6. The supernatant is removed, the lower precipitate is collected, and the precipitate is vacuum dried at 80°C for 12 hours. The final product is Ti 3 C 2 T x .
[0057] 2) Preparation of Nanostructured ZnPc
[0058] 2.5 mg ZnPc was dissolved in 2.5 mL DMF, and then the solution was ultrasonically treated (30 min). After that, the solution was added dropwise to 200 mL deionized water at a rate of 2 mL / min (which can be appropriately adjusted) and stirred continuously to form ZnPc nanostructures (3 h, 600 rpm can be appropriately adjusted). Finally, the deionized water, ethanol and acetone solutions were centrifuged and washed respectively, and the filtered product was vacuum dried at 80 ° C for 12 h.
[0059] 3) Ti 3 C 2 T x Preparation of ZnPc / ZnPc composite gas-sensitive materials
[0060] Take 2 mg of nanostructured ZnPc and 24 mg of multilayer Ti 3 C 2 T x The mixture was added to 30 mL of ethanol, ultrasonicated for 30 min, and then stirred with a magnet at 40 ° C and 500 rpm for 1 h, filtered to obtain a composite material, and the composite material was vacuum dried at 80 ° C for 12 h to obtain Ti 3 C 2 T x / ZnPc composite gas sensing material.
[0061] Example 4
[0062] A Ti 3 C 2 T x The / ZnPc composite gas-sensitive material is prepared according to the following steps;
[0063] 1) Ti 3 C 2 T x Preparation
[0064] Take 1g of Ti 3 AlC 2Slowly (about 20 min) add it to 20 ml HF and stir it magnetically (500 r / min) at room temperature for 22 h. Then, the stirred mixture is centrifuged and washed several times with deionized water at a speed of 3500 r / min until the pH of the supernatant is 5.5. The supernatant is removed, the lower precipitate is collected, and the precipitate is vacuum dried at 75 ° C for 12 h. The final product is multilayer Ti 3 C 2 T x .
[0065] 2) Preparation of Nanostructured ZnPc
[0066] 2.5 mg ZnPc was dissolved in 2.5 mL DMF, and then the solution was ultrasonically treated (30 min). After that, the solution was added dropwise into 200 mL deionized water at a rate of 2 mL / min (appropriately adjustable) and stirred continuously to form ZnPc nanostructures (3 h, 600 rpm can be appropriately adjusted). Finally, it was centrifugally washed with deionized water, ethanol and acetone solutions, and the filtered product was vacuum dried at 75 ° C for 12 h.
[0067] 3) Ti 3 C 2 T x Preparation of ZnPc / ZnPc composite gas-sensitive materials
[0068] Take 2 mg of nanostructure Z n P c and 12mg multilayer Ti 3 C 2 T x The mixture was added to 30 mL of ethanol, and after ultrasonication for 30 min, the mixture was stirred with a magnet at 35 ° C and 500 rpm for 1 h, and filtered to obtain a composite material. The composite material was vacuum dried at 75 ° C for 14 h to obtain Ti 3 C 2 T x / ZnPc composite gas sensing material.
[0069] Example 5
[0070] A Ti 3 C 2 T x The / ZnPc composite gas-sensitive material is prepared according to the following steps;
[0071] 1) Multilayer Ti 3 C 2 T x Preparation
[0072] Take 1g of Ti 3 AlC 2Slowly (about 20 min) add it to 20 ml HF and stir it magnetically (500 r / min) at room temperature for 26 h. Then, the stirred mixture is centrifuged and washed several times with deionized water at a speed of 3500 r / min until the pH of the supernatant is 6.5. The supernatant is removed, the lower precipitate is collected, and the precipitate is vacuum dried at 85 ° C for 12 h. The final product is multilayer Ti 3 C 2 T x .
[0073] 2) Preparation of Nanostructured ZnPc
[0074] 2.5 mg ZnPc was dissolved in 2.5 mL DMF, and then the solution was ultrasonically treated (30 min). After that, the solution was added dropwise into 200 mL deionized water at a rate of 2 mL / min (appropriately adjustable) and stirred continuously to form ZnPc nanostructures (3 h, 600 rpm can be appropriately adjusted). Finally, it was centrifugally washed with deionized water, ethanol and acetone solutions, and the filtered product was vacuum dried at 85 ° C for 12 h.
[0075] 3) Ti 3 C 2 T x Preparation of ZnPc / ZnPc composite gas-sensitive materials
[0076] Take 2 mg of nanostructured ZnPc and 24 mg of multilayer Ti 3 C 2 T x The mixture was added to 30 mL of ethanol, and after ultrasonication for 30 min, the mixture was stirred with a magnet at 45 ° C and 500 rpm for 1 h, and filtered to obtain a composite material. The composite material was vacuum dried at 75 ° C for 10 h to obtain Ti 3 C 2 T x / ZnPc composite gas sensing material.
[0077] Example 6
[0078] A Ti 3 C 2 T x The / ZnPc composite gas-sensitive material is prepared according to the following steps;
[0079] 1) Multilayer Ti 3 C 2 T x Preparation
[0080] Take 1g of Ti 3 AlC 2Slowly (about 20 min) add it to 20 ml HF and stir it magnetically (500 r / min) at room temperature for 22 h. Then, the stirred mixture is centrifuged and washed several times with deionized water at a speed of 3500 r / min until the pH of the supernatant is 5.5. The supernatant is removed, the lower precipitate is collected, and the precipitate is vacuum dried at 75 ° C for 12 h. The final product is multilayer Ti 3 C 2 T x .
[0081] 2) Preparation of Nanostructured ZnPc
[0082] 2.5 mg ZnPc was dissolved in 2.5 mL DMF, and then the solution was ultrasonically treated (30 min). After that, the solution was added dropwise to 200 mL deionized water at a rate of 2 mL / min (appropriately adjustable) and stirred continuously to form ZnPc nanostructures (3 h, 600 rpm can be appropriately adjusted). Finally, it was centrifugally washed with deionized water, ethanol and acetone solutions, and the filtered product was vacuum dried at 80 ° C for 12 h.
[0083] 3) Ti 3 C 2 T x Preparation of ZnPc / ZnPc composite gas-sensitive materials
[0084] Take 2 mg of nanostructured ZnPc and 20 mg of multilayer Ti 3 C 2 T x The mixture was added to 30 mL of ethanol, and after ultrasonication for 30 min, the mixture was stirred with a magnet at 35 ° C and 500 rpm for 1 h, and filtered to obtain a composite material. The composite material was vacuum dried at 75 ° C for 14 h to obtain Ti 3 C 2 T x / ZnPc composite gas sensing material.
[0085] Example 7
[0086] This embodiment provides a method for utilizing Ti 3 C 2 T x The process of preparing gas sensors using / ZnPc composite gas-sensitive materials, such as Figure 2 Ti 3 C 2 T x / ZnPc gas sensor preparation flow chart.
[0087] Ti 3 C 2 T x Preparation of ZnPc / ZnPc gas sensor
[0088] Take 0.5 g of Ti 3 C 2 T x / ZnPc and add it to 5 ml of absolute ethanol. Then, ultrasonicate it in an ultrasonic machine for 2 - 5 min to form a uniform slurry. Next, evenly coat the slurry onto an Al 2 O 3 ceramic tube with Au electrodes. During this process, ensure that the Au electrodes are completely covered, and the coating thickness should also be kept as consistent as possible. Place the ceramic tube coated with the gas sensing material into a vacuum drying oven. At 80 °C, maintain the vacuum for 6 h to ensure that the absolute ethanol completely evaporates. After drying, weld the four Pt wires of the ceramic tube to the corresponding positions on the device base. Then, pass the Ni - Cr alloy coil for heating through the ceramic tube and weld it to the base to obtain the Ti 3 C 2 T x / ZnPc gas sensor.
[0089] <SEM Morphology Analysis>
[0090] To more clearly observe the microstructure of the Ti 3 C 2 T x / ZnPc gas sensor, the morphology and microstructure of the Ti 3 C 2 T x / ZnPc composite gas - sensitive material were studied using a scanning electron microscope. Figure 1 (a, b, c) are SEM images of the Ti 3 C 2 T x / ZnPc composite gas - sensitive material at different magnifications. As can be seen from Figure 1 it, the Ti 3 C 2 T x support obtained by etching the MAX phase with hydrofluoric acid presents an accordion - like shape, with an obvious layered structure. Moreover, ZnPc nanoparticles are evenly attached to the multi - layer Ti 3 C 2 T x interlayers and the surface. The doping of ZnPc nanoparticles can provide more ion channels, accelerate charge transfer, and improve the gas - sensing performance. Figure 1 (d) is the morphological feature of the multi - layer Ti 3 C 2 T x after hydrofluoric acid etching. As can be seen from Figure 1 it, the etched multi - layer Ti 3 C 2 T xIt is accordion-shaped and has no impurities on the surface and inside, indicating that Ti has been prepared. 3 C 2 T x / ZnPc composite gas-sensitive material and Ti 3 C 2 T x gas sensing material.
[0091] <Working Principle of WS30B Gas Sensor Tester>
[0092] The test system is mainly based on the voltage test method and can record the change of the component resistance at the same time. The basic principle is shown in Figure 3 . Vh is the heating voltage provided by the gas sensor test system, and Vc is the test voltage, which is kept constant at 5V in this experiment. By measuring the voltage Vout of the load R1 connected in series with the gas sensor device, the resistance of the component is calculated by the formula R = (Vc - Vout) / (Vout / R1). In actual tests, the change in the partial voltage caused by the change in the resistance of the component R can also be indirectly recorded by recording the relationship between the voltage Vout on the load resistor R1 and the time t, so as to reflect the gas sensitivity of the component.
[0093] <XRD Phase Analysis>
[0094] In order to analyze whether the synthesized Ti 3 C 2 T x / ZnPc is successfully prepared, it is first studied through the XRD pattern. Figure 4 (a) is the XRD pattern of the prepared ZnPc nanostructure, which is in good agreement with the diffraction peaks on the ZnPc pattern reported in the literature, indicating that the prepared nanostructured ZnPc is successful. Figure 4 (b) is the XRD pattern of Ti 3 C 2 T x and Ti 3 C 2 T x / ZnPc. It can be seen from the figure that the characteristic peaks in Ti 3 C 2 T x all correspond one by one in Ti 3 C 2 T x / ZnPc, and the characteristic peaks of ZnPc all appear in Ti 3 C 2 T x / ZnPc without other impurity peaks, indicating that the preparation of Ti 3 C 2 T x / ZnPc is successful. Ti 3 C 2 Tx The intensity of the 002 diffraction peak decreased, which may be due to the doping of ZnPc, resulting in a decrease in the relative content of Ti 3 C 2 T x .
[0095] <XPS Energy Spectrum Analysis>
[0096] To further study the composition and chemical valence states of the gas-sensitive material, the XPS spectra of three samples, namely Ti 3 C 2 T x / ZnPc, ZnPc, and Ti 3 C 2 T x , were measured. As Figure 5 shown, after the C peak of Ti 3 C 2 T x / ZnPc was superimposed with the C peaks of ZnPc and Ti 3 C 2 T x , the relative content of the C element increased; there were no N and Zn elements in the XPS spectrum of Ti 3 C 2 T x , while Ti 3 C 2 T x contained these two elements, and the peaks of the elements in Ti 3 C 2 T x / ZnPc corresponded one by one to those in Ti 3 C 2 T x , indicating the successful synthesis of Ti 3 C 2 T x / ZnPc.
[0097] The C1s peaks of Ti 3 C 2 T x / ZnPc and ZnPc were deconvoluted using a deconvolution software to obtain their XPS energy spectra, and the results are as Figure 6 shown. Figure 6 (a) shows the C1s XPS spectrum of Ti 3 C 2 T x / ZnPc, where 281.4 eV, 284.6 eV, 286.3 eV, and 288.6 eV correspond to the C-Ti, C═C, C-N, and C═O chemical bonds, respectively. Figure 6(b) shows the C1s XPS spectrum of ZnPc, 284.6 eV, 286.3 eV and 288.6 eV correspond to C=C, CN and C=O chemical bonds, respectively. 3 C 2 T x The C1s spectrum of ZnPc contains Z n P c The CN peak in the sample is reduced, which may be due to the fact that ZnPc 3 C 2 T x After compounding, part of its CN bonds are converted into other chemical bonds such as C-Ti bonds, resulting in a decrease in the relative content of CN bonds.
[0098] <Gas Sensitivity Comparison for Ammonia>
[0099] In order to determine whether the gas sensor after the composite material is better than pure Ti 3 C 2 T x The gas sensor has a good response to ammonia and determines the optimal doping ratio. The Ti prepared in Example 1, Example 2, and Example 3 are respectively 3 C 2 T x / ZnPc composite gas sensitive material for preparing gas sensors 3 C 2 T x Preparation of gas sensor. The Ti prepared in Example 1 3 C 2 T x Ti / ZnPc composite gas sensing material 3 C 2 T x / ZnPc-6, Ti prepared in Example 2 3 C 2 T x Ti / ZnPc composite gas sensing material 3 C 2 T x / ZnPc-10, Ti prepared in Example 3 3 C 2 T x Ti / ZnPc composite gas sensing material 3 C 2 T x / ZnPc-12.
[0100] Tested Ti 3 C 2 T x / ZnPc-6、Ti 3 C 2T x / ZnPc-10、Ti 3 C 2 T x / ZnPc-12 and Ti 3 C 2 T x The response curves of the gas sensors made of these four gas-sensitive materials to five concentrations of ammonia at room temperature. Figure 7 It can be seen that with the NH 3 With the increase of NH concentration, several gas sensors with different doping ratios 3 The response of pure Ti 3 C 2 T x Gas sensor for NH 3 The response of NH 3 The response value of the three gas sensors with different doping ratios to the same concentration of ammonia is Ti 3 C 2 T x / ZnPc-10>Ti 3 C 2 T x / ZnPc-6>Ti 3 C 2 T x / ZnPc-12, 1:10 doped Ti 3 C 2 T x / ZnPc-10 gas sensor has the best response to ammonia, and the response value to 100ppm ammonia at room temperature can reach about 25%. Therefore, the following analysis and test will focus on Ti 3 C 2 T x / ZnPc-10 gas sensor for analysis.
[0101] <Humidity Impact Test>
[0102] In practical applications, the humidity of the detection environment is not constant, which puts forward requirements for the moisture resistance of the gas sensor. Therefore, the gas-sensing performance of the sensor is studied by changing the humidity of the WS30B test chamber. The specific steps are to add distilled water to the evaporation table of the gas-sensitive tester and accelerate its evaporation by heating. Since the test chamber is sealed, the humidity will increase. Figure 8 Shown is Ti 3 C 2 T x / The response value of ZnPc gas sensor to 100ppm ammonia at different humidity. As can be seen from the above figure, with the continuous increase of humidity, the gas sensitive response of the gas sensor changes, but generally tends to be stable.
[0103] <Gas Selectivity Test>
[0104] Selectivity refers to the degree of differentiation of the response size of the gas sensor when it comes into contact with the target gas and non-target gas. Fig. 9 As shown in the figure, the gas-sensing performance of the Ti was tested for different gases such as 100 ppm ammonia, DMF, acetone, toluene, formaldehyde, and ethanol at room temperature to study the 3 C 2 T x / ZnPc gas sensor selectivity. The results show that the Ti 3 C 2 T x The order of response of the ZnPc gas sensor to different gases is ammonia > formaldehyde > acetone > DMF > ethanol > toluene. The best response is to 100ppm ammonia at room temperature, with a response value of 25%, while the response to other gases is less than 5%. This shows that this type of gas sensor has excellent gas-sensitive response selectivity.
[0105] <Response recovery curve>
[0106] A gas sensor with good performance needs to have a fast response capability when encountering the target gas to be detected. Fig.10 It shows that Ti 3 C 2 T x / ZnPc gas sensor for 100ppm NH 3 The response recovery curve. Fig.10 It can be seen that at room temperature, 3 The response time is 74s and the recovery time is 418s, which is a relatively quick response.
[0107] <Repeatability test>
[0108] Repeatability is also an important indicator for evaluating the reliability of gas sensors. We studied the repeatability of the gas sensor in four consecutive tests of 100ppm ammonia gas at room temperature. Fig.11 As can be seen, the four consecutive cycles showed similar response values and a stable baseline, indicating that Ti 3 C 2 T x / ZnPc gas sensor for NH 3 The response is continuously repeatable.
[0109] Multilayer Ti was obtained by etching the MAX phase with hydrofluoric acid 3 C 2 T x Gas sensing material, Ti was successfully prepared by composite nanostructured ZnPc 3 C 2 T x / ZnPc gas sensor, and then characterized the phase, chemical valence state and morphology of the composite material, and tested and analyzed its gas sensing performance, and obtained the following conclusions:
[0110] (1) XRD analysis shows that the preparation of the composite material is successful. 3 C 2 T x The unique diffraction peaks of pure ZnPc are on Ti 3 C 2 T x / ZnPc, and the positions of the diffraction peaks can match.
[0111] (2) XPS analysis shows that within the measurement range (0-1200 eV), pure Ti 3 C 2 T x The elements detected in pure ZnPc are 3 C 2 T x / ZnPc, and the binding energy positions corresponding to each element can correspond one to one.
[0112] (3) SEM analysis shows that Ti 3 C 2 T x It exists in the composite and has a complete layered structure. It exists as a supporting substrate for the nanostructured ZnPc. The nanostructured ZnPc is uniformly attached to the multilayer Ti 3 C 2 T x surface or between layers.
[0113] (4) The gas-sensing test results show that the prepared Ti 3 C 2 T x / ZnPc gas sensor has better gas sensitivity than pure Ti 3 C 2 T x The gas sensor is much higher, and the response to 100ppm ammonia at room temperature can reach about 25%. The selectivity of the gas sensor to different gases was tested at room temperature. The results showed that the sensor has excellent selectivity to ammonia. In addition, Ti 3 C 2 T x / ZnPc gas sensors also have excellent moisture resistance and stability.
[0114] In the present invention, metal phthalocyanine is a class of organic semiconductor compounds whose chemical structure consists of four isoindole units. Its structure has great adjustability, and different properties can be obtained by introducing different peripheral or non-peripheral substituents or changing the central metal. The interaction between the phthalocyanine ring and the metal center can increase the carrier transfer rate, so that it exhibits excellent physical and chemical properties in energy storage and energy conversion systems, such as high charge mobility and redox characteristics. However, the relatively low conductivity of the metal phthalocyanine sensing material will reduce the electron transfer rate during the redox process, so that the prepared capacitor has only a low specific capacitance and energy density, thereby limiting its application in practice. The present invention enhances the redox characteristics of the metal phthalocyanine electrode sensing material by compounding the metal phthalocyanine with a conductive sensing material.
[0115] Ti 3 C 2 T x It is a new type of conductive two-dimensional transition metal carbide, Ti 3 C 2 T x It has surface hydrophilicity, high conductivity, excellent mechanical properties and flexibility, and is therefore considered a candidate sensing material to replace carbon. 3 C 2 T x The introduction of interlayer spacers such as nanoparticles between layers can effectively prevent the restacking effect and increase the Ti 3 C 2 T x Electrochemically active sites on the surface. Metallophthalocyanine has an 18-π aromatic electron cloud that can easily bind to Ti through π-π interactions. 3 C 2 T x Coordination and improved electrochemical response to charge storage by adding one-dimensional nanostructured metal phthalocyanines to Ti 3 C 2 T x The sheet has a significant enhancement effect on the ion mobility during the electrochemical redox process.
Claims
1. A Ti3C2T x The application of / ZnPc composite gas-sensitive material in ammonia detection is characterized in that: The Ti3C2T x / ZnPc composite gas sensing material with multilayer Ti3C2T x As the substrate, multilayer Ti3C2T x Interlayer doped nanostructured ZnPc.
2. The Ti3C2T according to claim 1 x The application of / ZnPc composite gas-sensitive material in ammonia detection is characterized in that: Apply the Ti3C2T on the sensor ceramic tube of the gas sensor x / ZnPc composite gas sensing material.
3. The Ti3C2T according to claim 1 x The application of / ZnPc composite gas-sensitive material in ammonia detection is characterized in that: The Ti3C2T x The preparation method of the ZnPc composite gas-sensitive material comprises the following steps: S1. Nanostructured ZnPc and multilayer Ti3C2T x The mixture was added to ethanol and ultrasonicated to obtain an intermediate solution; S2, magnetically stirring the intermediate solution after ultrasonic treatment in S1 at 35-45° C., and filtering to obtain a composite material; S3, vacuum drying the composite material at 75-85°C for 10-14h to obtain the Ti3C2T x / ZnPc composite gas sensing material.
4. The Ti3C2T3 according to claim 3 x The application of / ZnPc composite gas-sensitive material in ammonia detection is characterized in that: Nanostructured ZnPc and multilayer Ti3C2T x The mass ratio is 1:6 ~ 1:
12.
5. The Ti3C2T3 according to claim 3 x The application of / ZnPc composite gas-sensitive material in ammonia detection is characterized in that: The time of ultrasonic treatment in step S1 is 25 to 35 minutes.
6. The Ti3C2T3 according to claim 3 x The application of / ZnPc composite gas-sensitive material in ammonia detection is characterized in that: In step S2, the rotation speed of the magnetic stirring is 450-550 rpm, and the stirring time is 0.8-1.2 h.
7. The Ti3C2T3 according to claim 3 x The application of / ZnPc composite gas-sensitive material in ammonia detection is characterized in that: The multilayer Ti3C2T x The preparation process is as follows: S11, adding Ti3AlC2 to HF and magnetically stirring at room temperature for 22 to 26 hours; S12, washing the mixed solution after magnetic stirring in S11 with deionized water by centrifugation until the pH value of the supernatant is between 5.5 and 6.5, removing the supernatant and collecting the lower precipitate; S13, the lower precipitate collected in S12 is vacuum dried at 75-85°C, and the final product is multilayer Ti3C2T x .
8. The Ti3C2T3 according to claim 3 x The application of / ZnPc composite gas-sensitive material in ammonia detection is characterized in that: The preparation process of the nanostructured ZnPc is as follows: S21, dissolving ZnPc in DMF, and then ultrasonicating; S22, adding the solution after ultrasonic treatment in S21 dropwise into deionized water, and stirring to form a ZnPc nanostructure suspension; S23, washing the ZnPc nanostructure suspension in S22 with deionized water, ethanol and acetone solution by centrifugation and filtering, and vacuum drying the filtered product at 75-85° C. to obtain nanostructured ZnPc.
9. The Ti3C2T3 according to claim 8 x The application of / ZnPc composite gas-sensitive material in ammonia detection is characterized in that: In step S22, the solution is added dropwise into deionized water at a rate of 2 ml / min, and stirred at a rotation speed of 600 rpm for 2.8 to 3.2 h.
Citation Information
Patent Citations
Metal phthalocyanine-MXene composite material, supercapacitor and preparation method thereof
CN111763213A